Improving Student Mathematics Learning Outcomes Through the Integration of Islamic Values At Krueng Buloh Cut 1 Public Elementary School - Nursiah Nursiah; Fitri Yulianda (Jurnal Bionatural, 2025)
This study aims to analyze the improvement of mathematics learning outcomes through the integration of Islamic values among students of SD Negeri 1 Krueng Buloh Cut. The researcher conducted Classroom Action Research (CAR) as an effort to create active, creative, and innovative learning that can enhance students’ interest in learning mathematics by integrating Islamic values into the teaching process. The CAR was carried out in two cycles. Each cycle consisted of planning, action, observation, and reflection. The results of the study showed that integrating Islamic values into mathematics learning on the topic of fraction operations could improve the learning interest of fifth-grade students at SD Negeri 1 Krueng Buloh Cut. This was demonstrated by the findings, where in the first cycle the average score reached 72 with 83% of students achieving mastery, while in the second cycle the average score increased to 95 with 100% of students achieving mastery. From the first to the second cycle, there was an increase of 23 points, proving that integrating Islamic values into the topic of fraction operations successfully improved the learning outcomes of fifth-grade students at SD Negeri 1 Krueng Buloh Cut